Business Executives’ Evaluation of the Impact of Local Authorities’ Regulations on the Local Business Environment - Cosmin Florin Lehene; Răzvan Liviu Nistor (Transylvanian Review of Administrative Sciences, 2025)
This paper investigates the relationship between the regulation of the local economy by local policymakers and the appropriateness of local economic conditions for firms to compete nationally and internationally. We statistically analyzed the answers provided directly by the managers of 67 medium and large companies operating in Romania and found that regulation of the local economy is positively and significantly associated with the right local conditions for productivity (r = 0.548), innovation (r = 0.667), cluster formation (r = 0.574) and local competition (r = 0.760). Specifically, locations and cities where business executives reported better scores for private sector involvement in regulation, supporting export industries and specialized regulation also reported better scores for finding appropriate local conditions. Even so, 50% to 60% of business executives reported that their local economy is not regulated as it should be for their companies to be productive and innovative. Consequently, we propose various recommendations for local public policies. The research is important for both theory and practice of public administration, contributing with empirical evidence on improving aspects of local or urban economies for existing firms to increase their competitiveness for operating in national or international business contexts. Local policymakers find in this paper the specific aspects they should improve to stimulate local economic development by building microeconomic competitiveness.